PROTECTION OF THE RIGHT TO A SAFE ENVIRONMENT FOR LIFE AND HEALTH BY MEANS OF CRIMINAL LAW: ISSUES OF THEORY AND PRACTICE AT THE INTERNATIONAL AND NATIONAL LEVELS - DROBUSH, IRYNA; KOLOS, MYKHAILO (Ehrlich's Journal, 2025)
The article is devoted to the criminal law protection of the human right to a safe environment for life and health. The author examines international and national mechanisms of legal regulation in this area, including environmental standards and principles such as «polluter pays» and the precautionary principle. The authors analyze the criminal law aspects of liability for environmental offenses, as well as the problems of law enforcement in Ukraine. Particular attention is paid to the role of the prosecutor's office in the investigation of environmental crimes, in particular in the context of Russia's armed aggression. The author suggests areas for improvement of legislation and law enforcement practice to strengthen criminal legal protection of the environment.